MANAJEMEN PRODUKSI PROGRAM AKADEMI DAI CILIK DALAM MENYAMPAIKAN PESAN DAKWAH PADA TELEVISI REPUBLIK INDONESIA - Purwanti Ningsih; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Dai Cilik Academy is s da’wah competition program that involves children as participants that comes from various schools at the Regency or city level through Riau Province. Da’wah religious programs generally only aired before and during Ramadhan, but this program also airs every Sunday at Studio 2 TVRI Riau. In the middle of deficiency of children’s show program and religious education especially Islam, the Dai Cilik Academy program is present among the Riau community as an alternative spectacle for children so they can be emulated. The purpose of this study was to determine the management production of Dai Cilik Academy programs in delivering da’wah messages in Television of Republic Indonesia Riau Kepri.This study used qualitative research methods. Informants from this study were producers, event directors, presenters, jury, participants, and audience in the Dai Cilik Academy Program. While the object of this research is the management production of Dai Cilik Academy programs in delivering da’wah messages in Television of Republic Indonesia Riau Kepri. Data collection techniques used are observation, interview, and documentation. In achieving the validity of the data in this study, the authors use an extension of participation and triangulation.The results of the study show that the production planning for the Dai Cilik Academy program includes content planning, budget costs, facilities and time. The organizing stage is carried out, namely the division head. To realize the plans that have been prepared, continued with live broadcasts at Studio 2 TVRI Riau station by the crew, host, jury, and participants of the Dai Cilik Academy. The monitoring function is performed when major problems often occur after the production program is complete. This form of supervision is divided into positive and negative supervision. Keywords: Production Management, Dai Cilik Academy, Da’wah Messege.